# How do you solve #8(2w-6) + 4 (-1 - 5w)= 0#?

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 8(2w - 6) + 4(-1 - 5w) = 0, you first distribute the numbers outside the parentheses:

8(2w - 6) = 16w - 48 4(-1 - 5w) = -4 - 20w

Then, you combine like terms:

16w - 48 - 4 - 20w = 0 (16w - 20w) + (-48 - 4) = 0 -4w - 52 = 0

Next, you isolate the variable by adding 52 to both sides:

-4w - 52 + 52 = 0 + 52 -4w = 52

Then, you divide both sides by -4 to solve for w:

-4w / -4 = 52 / -4 w = -13

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7